Investigation on the effect of container configurations and forecastle fairings on wind resistance and aerodynamic performance of large container ships. Issue 1 (31st December 2022) - Deng, Rui; Song, Zhijie; Ren, Hang; Li, Hao; Wu, Tiecheng
Abstract : The wind resistance of a model of a large container ship was investigated experimentally and numerically under various conditions to investigate the aerodynamic performance and identify approaches for reducing wind resistance. The container ship model with and without six types of forecastle fairing was tested in a wind tunnel under conditions of full load and various uneven loads in different wind directions. The model test found that a specially designed forecastle fairing and certain container configurations are effective in reducing wind resistance. Then, a numerical simulation was performed to investigate the characteristics of the flow field around the test model. The comparisons and analyzes of the pressure distribution, streamlines, and vortex structure illuminate the mechanism of load reduction caused by the forecastle fairing and container configurations that are useful for reducing wind resistance. The optimization of a container ship for wind resistance is dominated by the effect of the container configuration; the contributions of forecastle fairing are secondary. When the overall effects of forecastle fairing and container configuration are considered, the streamlined load is the variant most optimized for wind resistance.